APPLICATION OF NANOTECHNOLOGY IN BUILDING CONSTRUCTION INDUSTRY - Jasimuddin, Md; Ali, Amir; Zaman, Danish; Feroz, Md Tasavvuf (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Important feats in the construction industry were the invention of concrete in ancient Rome, the mass production of steel from the mid-19th century and the mass-production of glass panes that changed from luxury to strength, likely others have similarly small to large changes with time. The paper focuses on questions like: What is nanotechnology? What can nanotechnology mean for the construction industry? Are there presently any commercialized products in construction that make use of nanotechnology? Construction can be defined as a process of converting the basic civil engineering raw materials to the final civil engineering product. Hence if the performance of the basic civil engineering raw materials is enhanced anyhow, the productivity will get increased as to work with those modified materials and the performance of the final civil engineering product will also be improved. Thus, the information presented in this paper is categorized into following main or basic raw materials: Cement, steel, paints, glass and fire protection materials, along with various definitions and basic concept of Nanotechnology.